2002
DOI: 10.1097/00007890-200204270-00028
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cardiovascular disease associated with proteinuria in renal transplant patients

Abstract: Proteinuria in the general population has been shown to be associated with cardiovascular disease, which is the main cause of death in renal transplantation. We investigated the effect of proteinuria on cardiovascular disease after renal transplantation in 532 renal transplant patients with functioning grafts for more than 1 year. Patients were classified into two groups depending on the presence of persistent proteinuria. We analyzed graft and patient survival, posttransplantation cardiovascular disease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 10 publications
7
55
1
3
Order By: Relevance
“…In renal transplantation, the presence of proteinuria at 12 mo is associated with a twofold risk of CV death [147] . Furthermore, persistent proteinuria is pre dictive of subsequent IHD and PVOD [148] . Even lowgrade proteinuria detected at early time points after renal transplantation is associated with inferior graft and patient outcomes [149] .…”
Section: Proteinuriamentioning
confidence: 99%
“…In renal transplantation, the presence of proteinuria at 12 mo is associated with a twofold risk of CV death [147] . Furthermore, persistent proteinuria is pre dictive of subsequent IHD and PVOD [148] . Even lowgrade proteinuria detected at early time points after renal transplantation is associated with inferior graft and patient outcomes [149] .…”
Section: Proteinuriamentioning
confidence: 99%
“…It is also associated with higher risk for mortality and cardiovascular disease events (6,7). Accordingly, the 2009 Kidney Disease: Improving Global Outcomes (KDIGO) clinical practice guideline on the care of the kidney transplant recipient (8) suggested measuring urine protein excretion at least once within the first month after transplantation, then every 3 months during the first year, then annually thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Histologic studies showed slight glomerulopathy in the kidney grafts; electron microscopic examination indicated effacement of the foot processes of the podocytes even though the creatinine level was stable. 7 Similar to clinical situations in which proteinuria leads to a higher risk of death and cardiovascular disease events and is considered to be a predictor of graft loss, [8][9][10][11] in the xenogeneic model it is associated with post-transplant hypoproteinemia, resulting in severe ascites, pleural effusion, and increased susceptibility to infection. Thus, studies to determine the mechanism responsible for this phenomenon and the development of preventive strategies are crucial to the success of future xeno-transplantation studies.…”
mentioning
confidence: 99%